2014
DOI: 10.1007/978-3-662-44208-1_1
|View full text |Cite
|
Sign up to set email alerts
|

E-retailing Ethics in Egypt and Its Effect on Customer Repurchase Intention

Abstract: Abstract. The theoretical understanding of online shopping behaviour has received much attention. Less focus has been given to the formation of the ethical issues that result from online shopper interactions with e-retailers. The vast majority of earlier research on this area is conceptual in nature and limited in scope by focusing on consumers' privacy issues. Therefore, the purpose of this paper is to propose a theoretical model explaining what factors contribute to online retailing ethics and its effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 81 publications
(61 reference statements)
1
11
0
Order By: Relevance
“…power distance, uncertainty avoidance, individualism, and masculinity) and religiosity in forming consumer ethical ideology (idealism and egoism) as well as the influence of consumer's ethical ideology on his/her perceptions regarding the deceptive practices of online retailers (e.g. Swaidan et al, 2008;Khalifa and Liu, 2004;Loi et al, 2012;Ramsey et al, 2007;Vitell et al, 1993;Fatoki, 2014;Kung and Huang, 2013;Agag and Elbeltagi, 2014;Agag et al, 2016;Agag and El-Masry, 2016a,b). Three factors, namely, power distance, uncertainty, religiosity, individualism, and masculinity Swaidan et al, 2008;Malloy et al, 2014) stand out as important factors forming online customer ethical ideology.…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%
“…power distance, uncertainty avoidance, individualism, and masculinity) and religiosity in forming consumer ethical ideology (idealism and egoism) as well as the influence of consumer's ethical ideology on his/her perceptions regarding the deceptive practices of online retailers (e.g. Swaidan et al, 2008;Khalifa and Liu, 2004;Loi et al, 2012;Ramsey et al, 2007;Vitell et al, 1993;Fatoki, 2014;Kung and Huang, 2013;Agag and Elbeltagi, 2014;Agag et al, 2016;Agag and El-Masry, 2016a,b). Three factors, namely, power distance, uncertainty, religiosity, individualism, and masculinity Swaidan et al, 2008;Malloy et al, 2014) stand out as important factors forming online customer ethical ideology.…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%
“…For instance, findings from Darke and Ritchie (2007) showed that deceptive advertising engenders buyers' distrust. A number of studies (Ingram et al 2005;Ramsey et al 2007;Riquelme and Roman 2014;Agag and El-Masry 2016b;Agag and Elbeltagi 2014) found that deceptive selling actions decrease customer satisfaction and trust. We hypothesize that in the B2B context, when buyers believe that the online service provider is engaging in deceptive actions, such perceptions will lead to reduced relationship quality.…”
Section: Non-deception and Relationship Qualitymentioning
confidence: 99%
“…For example, Agag and Elbeltagi (2014) discussed the internet's impact on retailing from globalization, human resources, consumer behavior, and retail formats. Agag and Elbeltagi (2014) have provided a framework to systematically view the internet's impact on the retail market.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Agag and Elbeltagi (2014) discussed the internet's impact on retailing from globalization, human resources, consumer behavior, and retail formats. Agag and Elbeltagi (2014) have provided a framework to systematically view the internet's impact on the retail market. Roberts and Zahay (2012) categorized the unique characteristics of the internet for retail applications from three dimensions: technology infrastructure, channel integration, and market information.…”
Section: Discussionmentioning
confidence: 99%